Chronic early trauma impairs emotion recognition and executive functions in youth; specifying biobehavioral precursors of risk and resilience. (29th October 2022) - Motsan, Shai; Yirmiya, Karen; Feldman, Ruth
Abstract: Exposure to chronic early trauma carries lasting effects on children's well-being and adaptation. Guided by models on resilience, we assessed the interplay of biological, emotional, cognitive, and relational factors in shaping two regulatory outcomes in trauma-exposed youth: emotion recognition (ER) and executive functions (EF). A unique war-exposed cohort was followed from early childhood to early adolescence. At preadolescence (11–13 years), ER and EF were assessed and respiratory sinus arrhythmia (RSA), biomarker of parasympathetic regulation, was quantified. Mother–child dyadic reciprocity, child's avoidance symptoms, and cortisol (CT) were measured in early childhood. Trauma-exposed youth displayed impaired ER and EF abilities. Conditional process analysis described two differential indirect paths leading from early trauma to regulatory outcomes. ER was mediated by avoidance symptoms in early childhood and modulated by cortisol, such that this path was evident only for preadolescents with high, but not low, CT. In comparison, EF was mediated by the degree of dyadic reciprocity experienced in early childhood and modulated by RSA, observed only among youth with lower RSA. Findings pinpoint trauma-related disruptions to key regulatory support systems in preadolescence as mediated by early-childhood relational, clinical, and physiological factors and highlight the need to specify biobehavioral precursors of resilience toward targeted early interventions.